The Effect of the Climate Crisis on Social Mobility and Economic Well-Being - Iriana Bakti; Dilshod Tursunov; Ming Pong (Yayasan Adra Karima Hubbi, 2025)
The climate crisis has emerged as one of the most pressing global challenges, affecting not only environmental sustainability but also socio-economic structures across nations. Rising temperatures, extreme weather events, and ecological degradation have profound implications for vulnerable populations, particularly in terms of their capacity for social mobility and access to economic opportunities. This study examines the interconnectedness between climate change impacts and patterns of social and economic inequality, focusing on how environmental disruptions exacerbate barriers to upward mobility and reduce overall economic well-being. The main objective of this research is to analyze the extent to which climate-related stressors influence socio-economic dynamics, especially among low-income and marginalized communities. Using a mixed-methods approach, this study combines statistical analysis of secondary global data with case studies drawn from three climate-vulnerable regions: Southeast Asia, Sub-Saharan Africa, and Latin America. Quantitative data were sourced from global databases such as the World Bank and IPCC reports, while qualitative insights were obtained through structured interviews and local policy document analysis. Findings reveal a strong correlation between climate vulnerability and reduced social mobility. Communities exposed to recurrent climate shocks tend to experience diminished income security, disrupted education pathways, and limited employment opportunities. These effects are particularly acute in regions with weak institutional support and limited adaptive infrastructure. The study concludes that the climate crisis is not only an environmental issue but also a significant socio-economic threat that demands integrated policy responses. Addressing climate justice and economic resilience simultaneously is crucial to safeguarding future opportunities for upward mobility.